Anti-Inflammatory Flavonolignans from Triticum aestivum Linn. Hull - Ah-Reum Han; Yun-Seo Kil; Min Jeong Hong; Jisu Park; Hyeon Hwa Park; Chang Hyun Jin; Joo-Won Nam; Jin-Baek Kim (Applied Sciences, 2020)
Wheat (Triticum aestivum Linn.; Poaceae) is a very common and important food grain and ranks second in total cereal crop production. A large amount of wheat hull is produced after threshing that, as the non-food part of wheat, is agro-waste, accounting for 15~20% of the wheat. This study aimed at biologically and phytochemically investigating wheat hull for its valorization as a by-product. In our ongoing search for natural product-derived anti-inflammatory agents, T. aestivum hull was evaluated for its nitric oxide (NO) production inhibition in lipopolysaccharide (LPS)-activated RAW 264.7 cells, and the phytochemical investigation of the ethyl acetate fraction showing inhibitory effect led to the isolation of a flavone (1) and seven flavonolignans (2–8). Compounds 2–8 have not yet been isolated from Triticum species. All compounds were evaluated for their LPS-induced NO production inhibition, and 1, 2, 4, 6, and 8 exhibited inhibitory effects with IC50 values ranging from 24.14 to 58.95 μM. These results suggest the potential of using T. aestivum hull as a source for producing anti-inflammatory components, enhancing its valorization as a by-product.